Hubungan Status Pekerjaan Ibu dengan Berat Lahir Bayi di RSUP Dr. M. Djamil Padang - Yuliva Djauhar Ismail, Diah Rumekti (Berita Kedokteran Masyarakat (BKM), 2009)
Background: According  to 2002-2003  Indonesia Demography Health Survey  (IDHS),  the percentage distribution of women based  on  job  status  in  the  past  12 months  in West  Sumatera showed  that  57,5%  of woman was working,  2,4%  of woman was  not working  and 40,1%  of  the women  did  not work  at  all.  From  the  data,  it  is shown  that  the  percentage  of woman who working was  bigger  than woman who was  not working. Based  on various  researches,  a  job  that will  be  done  by  a woman  especially while  pregnant,  had  influence  toward  the weight  of  the  infant who will be  delivered.Objective: This  research was aimed  to  find out  the  relationship of  job status and  job  type of mother with  infant’s birth weight in RSUP Dr. M. Djamil Padang.Method: This was  an observational  research  that  used Prospective Cohort design.  The data was collected  in antenatal polyclinic  of RSUP Dr.M. Djamil Padang. The  population was  all pregnant women who  came  to  check their  pregnancies  to  antenatal  polyclinic  and  they were  clustered  based  on  job  status  and  job  type.  Every pregnant woman was observed  and  their  pregnancy  development  that was  started  in  the week  32 of  pregnancy until delivery was continually monitored. The  sample was  taken with  non probability  sampling and  consecutive sampling. The  independent variables were  job  status and  job  type  and  the  dependent variable was  infant’s  birth weight. The  confounding  variable were  education,  social  economy  status, women’s age,  parity,  gestation  age, women’s height, weight  gain,  nutrition  intake,  children  sex  and mother’s  disease during  pregnancy.Result: The  dif ference  of  birth weight  in  a mother works with  heavy  physical  activity  was  196.44  gram (p=0.000) which was  lower  than mother who  did  not work with  heavy  physical  activity,  and  the difference  of infant’s  birth weight  in  the  group  of mother who were  ill  during  pregnancy with  those who were  not  ill  in  their pregnancy period was 243.92  gram  (p=0.001). Male  infant who was  born had  difference  on  the  average of  birth weight  that was  97.24  gram  (p=0.015) which was  heavier  than  female  infant. The  increasing  gestation  age every  one week will  increase  infant’s  birth weight  45.34 gram  (p=0.021) and  increasing  of mother’s weight will increase  infant’s  birth weight with  47.12 gram  (p=0.000). The  increasing  nutrition  intake  every one  kilocalories will  increase  infant’s birth weight 0.56 gram  (p=0.000). R2 was 0.2729 which mean  that model  2 as  the  result of double  linear  regression  analysis  could explain  the  relationship  and predicted  infant’s birth weight with  27.29%.Conclusion: There was a  relationship between mother’s  job  status  (working or  not working)  and mother’s  job type  (heavy  physical activity  and  low  physical activity) with  infant’s  birth weight,  in which  infant’s  birth weight in working mother with  heavy  physical  activity was  lower  than  infant   with mothers who  did  not work with heavy  physical  activity.Keywords: job  status,  job  type and  infant’s birth weight